The Influence of Social Media on Cultural Change in Palembang, Indonesia - Maimunah, Siti (Enigma Institute, 2023)
Social media has become an important part of Indonesian people's lives. The use of social media has spread to various levels of society, from children to adults. This has given rise to various cultural changes in Indonesia, both positive and negative. This research uses a qualitative method with a case study approach. As many as 1000 teenagers aged 18-25 years were included in this study, where the research subjects underwent an online data collection process. Social media has become an important factor influencing cultural change in Palembang, Indonesia. This cultural change has complex implications for the people of Palembang, Indonesia, both positive and negative.